When Voluntary, Incentive-Based Controls Fail: Structuring a Regulatory Response to Agricultural Nonpoint Source Water Pollution - Douglas R. Williams (Washington University Journal of Law & Policy, 2002)
This Essay considers the extent to which more direct federal regulation of agricultural nonpoint source pollution is warranted. My first conclusion is that an increased federal presence is necessary. My second conclusion is that the costs of implementing such plans and practices should be distributed in a pragmatic way that recognizes the extraordinary organizational presence and political clout of the agricultural industry. Third, measures that promise water quality improvements beyond baseline regulatory requirements should be encouraged. Innovative programs such as point-nonpoint source pollution trading programs may yield sizeable environmental benefits at reduced costs, and states should be free to experiment with this sort of alternative.
Keywords: Agriculture; Nonpoint source pollution; Environmental policy; Pollution control; Water pollution; United States